Integrated cytomembrane proteomics identifies EpCAM/MGST1 as therapeutic targets in metastatic laryngeal carcinoma - Zhuang, Suling; Wu, Xiaobo; Lin, Xiaohuang; Li, Zhihan; Gan, Di; Wang, Shixin; Lin, Xue; Lin, Gongbiao; Gao, Miao (Frontiers in Genetics, 2025)
BackgroundLymph node metastasis plays a crucial role in cancer recurrence and survival, however, the underlying molecular mechanism and biomarkers in laryngeal carcinoma remain poorly characterized. While cytomembrane proteins represent attractive therapeutic targets due to their accessibility, the identification of tractable candidates for precision therapy remains challenging.MethodsThis study aimed to identify potential therapeutic targets for laryngeal squamous cell carcinoma (LSCC) with lymph node metastasis through cytomembrane proteome profiling. We conducted a comprehensive multi-omics analysis in 158 LSCC cases from TCGA (111 patients) and CPTAC (47 patients) database. The correlations between lymph node metastasis and molecular features at proteome levels were investigated. Potential immunotherapy targets were identified and prioritized using an in silico screening algorithm for cytomembrane proteome.ResultsThe in silico screening algorithm for cytomembrane proteome led to the recognition of EpCAM and MGST1 as potential targets. We demonstrated that EpCAM and MGST1 were abundantly expressed in LSCC, particularly in cases with lymph node metastasis. Functional siRNA knockdown confirmed their critical roles in driving in vitro proliferation, invasion, and migration. Furthermore, their knockdown hindered the Wnt/β-catenin and PI3K signaling pathways.ConclusionIntegrated cytomembrane proteomics in metastatic LSCC unveils EpCAM/MGST1 as actionable immunotherapeutic targets, with silencing attenuating oncogenic proliferation, invasion, and Wnt/β-catenin-PI3K crosstalk, offering novel therapeutic avenues.